Fundamental Rights vs. National Security: A Constitutional Dilemma - Muhammad Faiq Butt; Dr. Sajid Sultan; Jawad Khalil Pitafi; Muhammad Umair Razzaq (Social Science Review Archives, 2025)
This conflict between the importance of core rights on the one hand and the dictates of the national security on the other has been growing in recent decades especially on the states that are battling with the menace of terrorism, political instability as well as weak democratic institutions. Pakistan offers an interesting background to study this dilemma in the constitution. Although the Constitution of Pakistan provides an effective system of rights, the governments have been very quick to curtail civil liberties under the pretence of maintaining national security which has in most of the cases been done with less oversight and little accountability. This paper provides a critical analysis of the conceptual, constitutional and political aspects of this conflict and claims that an unmonitored pursuit of security is threat to the democratic spirit and social accord. It ends with the statement that to achieve a balance between state interest and individual freedom it would be necessary to have a calibrated law reform, transparency of institutions and international best practices.